Competitive Effects of Vertical Integration with Downstream Oligopsony and Oligopoly - Simon Loertscher; Markus Reisinger (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We analyze the competitive e?ects of backward vertical integration by a partially vertically integrated ?rm that competes with non-integrated ?rms both upstream and downstream. We show that vertical integration is procompetitive under fairly general conditions. It can be anticompetitive only if the ex ante degree of integration is relatively large. Interestingly, vertical integration is more likely to be anticompetitive if the industry is less concentrated. These results are in line with recent empirical evidence. In addition, we show that even when vertical integration is procompetitive, it is not necessarily welfare enhancing.
urn:nbn:de:bvb:19-epub-13276-2
Keywords: 330; Vertical Integration; Downstream Oligopsony; Downstream Oligopoly; Competition Policy; Capacity Choice